2011
DOI: 10.2478/s11532-010-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of changes in hydrophilic/hydrophobic balance and in chemical activity of HSA induced by thermal treatments

Abstract: Samples of human serum albumin (HSA) obtained as a result of heat denaturation followed by refolding controlled by a cooling of the protein solution were studied by several methods: chromatographic measurements, kinetic of the reaction with a water soluble free radical and by electron paramagnetic resonance (EPR) spectroscopy. In this context the interaction of this protein with β-cyclodextrin (β-CD) and sodium dodecyl sulfate (SDS) was also investigated. Reversed phase thin layer chromatography (RP-TLC) showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The ability of cyclodextrins to prevent or slow a protein aggregation process or otherwise inhibit the interaction between a protein and hydrophobic molecules has already been reported. , Cyclodextrins are capable of complexing hydrophobic moieties, which might be present in some cases at the surface of a protein. In our previous studies on the radical scavenging activity of BSA and HSA, a strong interaction between β-CD and albumins was not revealed. , …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The ability of cyclodextrins to prevent or slow a protein aggregation process or otherwise inhibit the interaction between a protein and hydrophobic molecules has already been reported. , Cyclodextrins are capable of complexing hydrophobic moieties, which might be present in some cases at the surface of a protein. In our previous studies on the radical scavenging activity of BSA and HSA, a strong interaction between β-CD and albumins was not revealed. , …”
Section: Resultsmentioning
confidence: 88%
“…The EPR spectra of CAT16 in BSA solutions reflect a superposition of (a) a component with narrow lines corresponding to the free CAT16 in solution, and (b) a component with broader lines due to restricted mobility, corresponding to the spin probe “bound” to albumin. The interaction of CAT16 with BSA is comparable to that of CAT16 with HSA, as the spectrum of CAT16 in a solution of 10 mg/mL HSA exhibits similar features . The experimental spectra of CAT16 in BSA solutions can be deconvoluted by subtracting the spectrum of CAT16 in buffer solution from the spectrum recorded in BSA (Figure ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The antioxidant activity of rosemary extract in water was tested in water using the water soluble derivative of DPPH, DPPH-SO 3 Na, which was previously used to evaluate the effect of temperature on the ability of albumins to reduce it (Ionita & Sahini, 2004;Sahini & Ionita, 2011). The UV-VIS spectra for a solution of DPPH-SO 3 Na in water recorded over 3 h revealed that the absorbance at the maximum absorption band of 520 nm was almost constant.…”
Section: Resultsmentioning
confidence: 99%
“…Walter et al (2011) recently reported an indirect proof of clay's role in prions' infectivity perpetuation by analyzing prion-infected deer herd data in the USA in relation to clay soil content. These components have been shown to change proteins' hydrophilic/hydrophobic balance and modulate the oligomerization of membrane proteins in lipid bilayers, which may explain why under basic conditions prions are inactivated (Sahini and Ionita, 2011;Otzen et al, 2007). In environmental water ecosystem (urban sewage and seawater) prions have been shown to have limited survival compared to in buffered solutions such as phosphate buffered saline (Maluquer de Motes et al, 2008).…”
Section: Bse and Environmentmentioning
confidence: 99%